Optical inhibition of motor nerve and muscle activity in vivo. Issue 6 (30th April 2013) - Liske, Holly; Towne, Chris; Anikeeva, Polina; Zhao, Shengli; Feng, Guoping; Deisseroth, Karl; Delp, Scott
Abstract Introduction: There is no therapeutic approach that provides precise and rapidly reversible inhibition of motor nerve and muscle activity for treatment of spastic hypertonia. Methods: We used optogenetics to demonstrate precise and rapidly reversible light‐mediated inhibition of motor nerve and muscle activity in vivo in transgenic Thy1::eNpHR2.0 mice. Results: We found optical inhibition of motor nerve and muscle activity to be effective at all muscle force amplitudes and determined that muscle activity can be modulated by changing light pulse duration and light power density. Conclusions: This demonstration of optical inhibition of motor nerves is an important advancement toward novel optogenetics‐based therapies for spastic hypertonia. Muscle Nerve 47: 916–921, 2013